2007
DOI: 10.1073/pnas.0702761104
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates matrix metalloproteinase-9 activity by guanylyl-cyclase-dependent and -independent pathways

Abstract: Matrix metalloproteinases (MMPs) are of central importance in the proteolytic remodeling of matrix and the generation of biologically active molecules. MMPs are distinguished by a conserved catalytic domain containing a zinc ion, as well as a prodomain that regulates enzyme activation by modulation of a cysteine residue within that domain. Because nitric oxide (NO) and derived reactive nitrogen species target zinc ions and cysteine thiols, we assessed the ability of NO to regulate MMPs. A dose-dependent, bipha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
153
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 43 publications
11
153
1
3
Order By: Relevance
“…Recently, a similar inhibition of MMP-9 activity by high concentrations of SPER-NO was reported, but a mechanism for inhibition was not investigated or suggested (28). Although MMP-9 inhibition was observed using relatively high concentrations of DETA-NO (500-1000 µM) or SPER-NO (100 µM), these concentrations of NO donors produce sub-micromolar steady state NO levels that are reflective of NO production by, for example, activated macrophages (22,28), and may thus be relevant to inflammatory conditions. Since MMPs are subject to inactivation by oxidative mechanisms (7,9,34), it may not be surprising that high concentrations of NO or RNS may similarly inactivate MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar inhibition of MMP-9 activity by high concentrations of SPER-NO was reported, but a mechanism for inhibition was not investigated or suggested (28). Although MMP-9 inhibition was observed using relatively high concentrations of DETA-NO (500-1000 µM) or SPER-NO (100 µM), these concentrations of NO donors produce sub-micromolar steady state NO levels that are reflective of NO production by, for example, activated macrophages (22,28), and may thus be relevant to inflammatory conditions. Since MMPs are subject to inactivation by oxidative mechanisms (7,9,34), it may not be surprising that high concentrations of NO or RNS may similarly inactivate MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of inflammatory cells may also be affected by the chemical modifications of matrix metalloproteinases (MMPs) (Ridnour et al 2007). Recently, NO may also affect lymphocyte migration by altering cell motility.…”
Section: No and The Immune Responsementioning
confidence: 99%
“…Generally, ROS activate MMPs by modifying the cysteine residue that stabilizes the inactive structure [59], although some studies supporting our results revealed a reduction of the activity of MMPs by tryptophan oxidation in the catalytic domain by ROS to restrain proteolytic activity during inflammation [60,61] or as a result of excessive protein oxidation, which led to protein degradation and altered the biological functions of MMPs. Because latent MMP-9 is proteolytically activated by MMP-1, the suppression of MMP-1 activity can be responsible for the decrease of MMP-9 activity together with the increased expression of TIMP-1 and high levels of NO [62]. Because the ECM plays a pivotal role in the cytoskeletal filament assembly, the changes induced by Si/SiO 2 QDs on MMPs expression and activity correlate with the alteration of the actin cytoskeleton [63].…”
mentioning
confidence: 99%